2021
DOI: 10.1155/2021/5528786
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Symptoms and Types of Samples Are Critical Factors for the Molecular Diagnosis of Symptomatic COVID-19 Patients: A Systematic Literature Review

Abstract: Background. Currently, a novel coronavirus found in 2019 known as SARS-CoV-2 is the etiological agent of the COVID-19 pandemic. Various parameters including clinical manifestations and molecular evaluation can affect the accuracy of diagnosis. This review aims to discuss the various clinical symptoms and molecular evaluation results in COVID-19 patients, to point out the importance of onset symptoms, type, and timing of the sampling, besides the methods that are used for detection of SARS-CoV-2. Methods. A sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 127 publications
0
13
0
Order By: Relevance
“…As the research on specific problems [ 63 65 ] related to COVID-19 is exponentially growing, use of reliable, cost effective and fast means of diagnosing the disease become very valuable. In order to meet this need, numerous non-molecular tests such as SARS-CoV-2 Ag-RDTs and SARS-CoV-2 Ag-IRRDTs have been introduced by different manufacturers in the worldwide market.…”
Section: Discussionmentioning
confidence: 99%
“…As the research on specific problems [ 63 65 ] related to COVID-19 is exponentially growing, use of reliable, cost effective and fast means of diagnosing the disease become very valuable. In order to meet this need, numerous non-molecular tests such as SARS-CoV-2 Ag-RDTs and SARS-CoV-2 Ag-IRRDTs have been introduced by different manufacturers in the worldwide market.…”
Section: Discussionmentioning
confidence: 99%
“…A molecular diagnostic, that is, real‐time polymerase chain reaction (RT‐PCR) that has been widely used as a gold standard of detection depends on the sampling locations, probes of SARS‐CoV‐2 gene sequence that is used as a target for detection and days of symptom onset. 5 Therefore, considering that RT‐PCR is complex, expensive, and slow to deliver, 6 an alternative diagnostic method that is more user‐friendly and cost‐effective, which permits new cases to be isolated immediately, is in high demand.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers concluded that despite the fact that the spread of the epidemic has been somewhat prevented and that it has progressed globally to vaccination and treatment, the adequacy of vaccines and treatments has not yet been determined. Therefore, early detection of infected people remains the key to limiting the epidemic [ 17 ]. Determining the prevalence of SARS-CoV-2 in blood donors enables the control of virus circulation in healthy individuals and helps implement strategies to reduce transmission, especially in the absence of seroprevalence surveys.…”
Section: Introductionmentioning
confidence: 99%